Exaggerated Exercise Blood Pressure as a Marker of Baroreflex Dysfunction in Normotensive Metabolic Syndrome Patients - Dutra-Marques, Akothirene C.; Rodrigues, Sara; Cepeda, Felipe X.; Toschi-Dias, Edgar; Rondon, Eduardo; Carvalho, Jefferson C.; Alves, Maria Janieire N. N.; Braga, Ana Maria F. W.; Rondon, Maria Urbana P. B.; Trombetta, Ivani C. (Frontiers in Neuroscience, 2021)
Introduction Exaggerated blood pressure response to exercise (EEBP = SBP ≥ 190 mmHg for women and ≥210 mmHg for men) during cardiopulmonary exercise test (CPET) is a predictor of cardiovascular risk. Sympathetic hyperactivation and decreased baroreflex sensitivity (BRS) seem to be involved in the progression of metabolic syndrome (MetS) to cardiovascular disease. Objective To test the hypotheses: (1) MetS patients within normal clinical blood pressure (BP) may present EEBP response to maximal exercise and (2) increased muscle sympathetic nerve activity (MSNA) and reduced BRS are associated with this impairment. Methods We selected MetS (ATP III) patients with normal BP (MetS_NT, n = 27, 59.3% males, 46.1 ± 7.2 years) and a control group without MetS (C, n = 19, 48.4 ± 7.4 years). We evaluated BRS for increases (BRS+) and decreases (BRS−) in spontaneous BP and HR fluctuations, MSNA (microneurography), BP from ambulatory blood pressure monitoring (ABPM), and auscultatory BP during CPET. Results Normotensive MetS (MetS_NT) had higher body mass index and impairment in all MetS risk factors when compared to the C group. MetS_NT had higher peak systolic BP (SBP) (195 ± 17 vs. 177 ± 24 mmHg, P = 0.007) and diastolic BP (91 ± 11 vs. 79 ± 10 mmHg, P = 0.001) during CPET than C. Additionally, we found that MetS patients with normal BP had lower spontaneous BRS− (9.6 ± 3.3 vs. 12.2 ± 4.9 ms/mmHg, P = 0.044) and higher levels of MSNA (29 ± 6 vs. 18 ± 4 bursts/min, P < 0.001) compared to C. Interestingly, 10 out of 27 MetS_NT (37%) showed EEBP (MetS_NT+), whereas 2 out of 19 C (10.5%) presented (P = 0.044). The subgroup of MetS_NT with EEBP (MetS_NT+, n = 10) had similar MSNA (P = 0.437), but lower BRS+ (P = 0.039) and BRS− (P = 0.039) compared with the subgroup without EEBP (MetS_NT−, n = 17). Either office BP or BP from ABPM was similar between subgroups MetS_NT+ and MetS_NT−, regardless of EEBP response. In the MetS_NT+ subgroup, there was an association of peak SBP with BRS− (R = −0.70; P = 0.02), triglycerides with peak SBP during CPET (R = 0.66; P = 0.039), and of triglycerides with BRS− (R = 0.71; P = 0.022). Conclusion Normotensive MetS patients already presented higher peak systolic and diastolic BP during maximal exercise, in addition to sympathetic hyperactivation and decreased baroreflex sensitivity. The EEBP in MetS_NT with apparent well-controlled BP may indicate a potential depressed neural baroreflex function, predisposing these patients to increased cardiovascular risk.